Application of oxidative and soda leach method for selective recovery of molybdenum from spent hydrodesulfurisation catalysts - Nui, Pham Xuan; Tung, Pham Son (Petrovietnam Journal, 2015)
The spent catalysts of these processes contain about 4 - 12 wt% molybdenum (Mo) and will bring economic benefi ts if the valuable metals are recovered. In this article, the authors investigate the process of molybdenum recovery from spent hydrodesulphurisation (HDS) catalyst using the mixture of sodium carbonate and hydrogen peroxide mixture. Molybdenum recovery is dependent on the concentration of Na2CO3, H2O2 and pH in the reaction medium. Under the appropriate reaction conditions as 40g/L Na2CO3; 6 vol.% H2O2, room temperature, and reaction time = 2 hours, a molybdenum yield of 85% could be achieved. Carbon was used as asorbent for the recovery of molybdenum from the leach solution. With this method, recovery of molybdenum as MoO3 product of 95% purity was achieved.